News Media and the Öresund Region - Falkheimer Jesper; Blach-Ørsten Mark; Eberholst Mads Kæmsgaard; Möllerström Veselinka (Nordicom Review, 2017)
This article presents a first attempt to investigate the news content and news routines of Danish and Swedish news media covering the Öresund region. From a theoretical perspective, the Öresund region can be considered a possible best-case example of what is categorised as horizontal Europeanisation, in other words, of the potential for increased communication linkages in news media content among European Union (EU) member states. We investigate this topic by analysing news content published by selected media outlets from 2002 to 2012 and by interviewing Danish and Swedish journalists who cover the region. We find that most news content does not mention the Öresund region, and that one reason for this lack might be that neither Danish nor Swedish reporters consider the region to be newsworthy.